Empowering Students as Sustainability Ambassadors: A Conceptual Framework for Higher Education - Alharbi, Hani (Journal of Sustainability Perspectives, 2025)
Universities have a crucial role in fostering sustainability awareness and solutions. This conceptual paper introduces a three-stage framework-Awareness, Action, and Advocacy-for empowering students as sustainability ambassadors. The Awareness stage focuses on building foundational knowledge through orientation programs, campus-wide campaigns, and interactive workshops. Action emphasizes hands-on engagement, from eco-clubs and recycling drives to collaborative green projects that cultivate leadership and problem-solving skills. The Advocacy stage involves peer education, institutional policy dialogue, and partnerships with local communities and organizations to extend the impact beyond the campus. The proposed framework aligns with global sustainability goals, including the UN Sustainable Development Goals (SDGs) and the UI GreenMetric World University Rankings criteria. It highlights the importance of administrative support, training, and recognition systems to sustain momentum and institutionalize these efforts. By systematically involving students in sustainability initiatives, universities can catalyze lasting cultural shifts, foster responsible citizenship, and create pathways for scalable, real-world impact. This paper contributes a strategic roadmap for higher education institutions seeking to harness student potential, address environmental and social challenges, and build a generation of skilled sustainability leaders.